The Effect of Pre-bankruptcy Financial Distress on Earnings Management Tools - Sara Hassanpour; Mehdi Nazemi Ardakani (International Review of Management and Marketing, 2017)
The purpose of this research is the effect of pre-bankruptcy financial distress on earnings management tools in the listed companies in Tehran stock exchange. The sample of this study is 133 of listed companies in Tehran stock exchange in which have been examined during 2010 to 2014. In this research, independent variable is pre-bankruptcy financial that is estimated according to the criteria of Staw et al (1983) and earnings management tools as dependent variable include real activity manipulation and accrual manipulation were considered. Independent T test was used in econometric software Eviews 9 to test the research hypotheses. The results of this hypothesis showed that there was a significant positive relationship between pre-bankruptcy financial distress and real activities management and accrual manipulation.